(untitled) - Shah, Kanti L. (New Jersey, 2000)
This easy-to-read and pragmatic book offers a systematic treatment of solid and hazardous waste management technology. Encouraging self-learning, with a focus on current technical and scientific fundamentals, it covers all the basic concepts and tools needed for making decisions. Chapter topics include environmental legislation and regulations; sources; composition and characteristics; physical, chemical, and biological properties; storage, collection and transportation; processing technologies; source reduction and reuse; disposal; and management and control of landfill leachate and gas. For civil engineers and scientists facing a first time involvement in any aspect of solid and hazardous waste management, this book will be a valuable reference.
Keywords: Refuse and refuse disposal,Hazardous wastes management industry